Studi Literature Review: Implementasi Teknologi Digital di Sekolah Dasar - M. Alfarisi; Syarifuddin; Syahru Ramadhan (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study examines the development of digital technology implementation in primary schools based on available literature from 2020 to 2024. The main focus of this research is to understand how digital technology implementation has evolved in primary schools. The research method used is qualitative content analysis with a systematic literature review (SLR) approach and article analysis using Vosviewer. The analysis method includes the examination of Scopus publication data based on year, author, country, and topic clusters, trending topics, and mapping. The results of the study show a significant increase in the number of publications related to digital technology in primary schools, especially from 2022 to 2024, influenced by the impact of the COVID-19 pandemic which accelerated the need for remote learning. Additionally, the dominance of leading authors and countries such as Indonesia, the United States, and Brazil highlights the concentration of intense research in countries that are more actively integrating technology into primary education. Topic mapping reveals that the main focus of research is on the impact of technology on teaching practices and students' learning experiences, as well as evaluating its effect on task performance and student motivation. This research contributes to enriching the discourse on digital technology in primary schools and emphasizes the importance of further evaluation regarding the effectiveness and practical applications of technology in enhancing the quality of education. The study also identifies the need for further research on the challenges of implementing technology in developing countries and more effective integration strategies.